Fundamentals of Renal Pathology - Fogo, Agnes; Bruijn, Jan A.; Cohen, Arthur H.; Colvin, Robert B.; Jennette, J. Charles (Springer New York : Imprint: Springer, 2007)
Fundamentals of Renal Pathology will provide the general pathologist, pathology residents and fellows in training, the renal pathologist, and the nephrologist and nephrology resident, with a compact and up-to-date resource on the basics of renal pathology. Beginning with the basic concepts and methods in renal pathology, the text covers renal anatomy, including gross and miscroscopic appearance and pathogenic mechanisms in renal diseases. Abundantly illustrated with 107 photographs, 84 of which are in color.